Author Correction: Factors of the bone marrow microniche that support human plasma cell survival and immunoglobulin secretion - Doan C. Nguyen (Nature Portfolio, 2019)
The original version of this Article omitted a declaration from the Competing Interests statement, which should have included the following: ‘A patent has been applied for by Emory University with F.E.L, I.S. and D.C. N. as named inventors. The patent application number is PCT/US2016/036650’. This has now been corrected in both the PDF and HTML versions of the Article.